Promoting a Culture of Lawfulness: Review of the International Workshop on Utilizing the E4J Training Mod- ules in Central European Higher Education - Mohay, Ágoston; Szijártó, István (Pécs journal of international and European law, 2021)
The Centre for European Research and Education of the Faculty of Law of the University of Pécs organised an international training workshop on utilizing the E4J training modules in Central European higher education. It focused on five module series of the Education for Justice (E4J) initiative which was developed by the UNODC to achieve goals set out in the Doha Declaration. The workshop introduced, discussed and evaluated the E4J training module series regarding or- ganised crime, crime prevention and criminal justice, counterterrorism, trafficking in persons and smuggling of migrants and cybercrime, with the participation of seven universities from five Cen- tral-European countries. The aim of the workshop was to formulate recommendations on how best to utilise E4J training modules in tertiary education.